PATTERN OF INJURIES IN COUNTER TERRORISM OPERATIONS: AN EXPERIENCE AT A TERTIARY CARE HOSPITAL - Butt, Muhammad Qasim; Chatha, Sohail Saqib; Ghumman, Adeel Qamar; Farooq, Mahwish (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the pattern of injuries sustained by military persons in counterterrorism operations. Study Design: Descriptive study with retrospective data collection. Place and Duration of Study: The study was carried out at Combined Military Hospital (CMH) Kohat over a period of four years from December 2008 to December 2012. Material and Methods: Data of patients was collected by noting the injuries suffered by soldiers and officers evacuated from operational area and their outcome after treatment in tertiary care hospital from hospital papers. Results: Total of 1226 patients were received from operational area over a period of 4 years from December 2008 to December 2012. One hundred and fifty seven (12.8%) were brought in dead while 1069 (87.2%) were received alive. Twelve (0.98%) patients died during hospital treatment. All patients were male. A total of 593 (48.4%) suffered limb injuries, 50 (4.1%) suffered neck injuries, 61(5%) had chest injuries, 30 (2.4%) suffered head injuries, 62 (5%) presented with abdominal injuries, 52 (4.3%) suffered eye and face injuries, 3 (0.2%) suffered acoustic trauma, 9 (0.7%) had vascular injuries while 366 (29.8%) suffered multiple injuries. In 480 (39.2%) patients mechanism of injury was fire arm injuries, 34 (2.8%) suffered road traffic accidents while in 712 (58.1%) injury was caused by Improvised Explosive Device. Conclusion: There is a shift in the pattern of injuries in modern warfare therefore necessary training of medical staff is required along with speedy evacuation of patients to tertiary care hospitals.